Duration of protection against Bordetella pertussis infection elicited by whole-cell and acellular vaccine priming in Polish children and adolescents. Issue 41 (1st October 2021) - Paradowska-Stankiewicz, Iwona; Rumik, Agnieszka; Bogusz, Joanna; Zbrzeźniak, Jakub; Rastawicki, Waldemar; Śmietańska, Karolina; Vargas-Zambrano, Juan C.; Macina, Denis
Highlights: Acellular and whole-cell pertussis vaccines are both used for infant vaccination in Poland. Serological signs of vaccination or infection were analyzed by time since last vaccine. Vaccine-induced antibodies wane at a similar rate in wP-primed and aP-primed children. In both groups, serological markers of infection increase around the same age. Protection appears to persist for a similar duration in the aP-primed and in the wP-primed groups. Abstract: Background: In the context of reported resurgence of pertussis in the last decade, researchers hypothesized that acellular (aP) pertussis vaccines elicit a shorter-lived protection compared to whole-cell (wP) pertussis vaccines. However, in the studies seeking to demonstrate this hypothesis, exposure to each vaccine type was not concurrent, and contradictory epidemiologic modeling questioned its validity. The context of pertussis vaccination history in Poland, with both vaccine types used concurrently in comparable proportions, provided an opportunity to investigate this hypothesis. We sought to compare waning of protection by primary series vaccine type by measuring anti-pertussis toxin antibody concentrations as proxy for recent infection. Materials and methods: Serological samples from 2, 745 children and adolescents aged ≥5 years and <16 years and with completed 5-dose pertussis vaccination series were tested by ELISA for pertussis toxin (PT) antibodies. Participants were stratified by type of priming vaccine (wP or aP). Vaccination timeliness and priming-specific trends in anti-PT antibody levels by time since last vaccine dose were analyzed. Results: A total of 1, 161 (42.5%) children received wP vaccines, and 1, 314 (48.1%) received aP vaccines for their primary series and toddler booster. Overall, 53.57% of the subjects received doses 2–4 in a timely manner, while only 41.52% received all 5 doses at the recommended intervals. Using GMCs or seropositivity measures, both priming groups showed a re-increase in anti-PT antibody levels signing infection in recent years from 8 years after the school-entry booster onward. Comparisons did not show any significant differences between the two groups in the timing or intensity of this re-increase. Conclusion: Our results clearly confirm that vaccine-elicited immunity against pertussis wanes among adolescents even after a complete infant, toddler and school-entry vaccination series. The timing and intensity of the waning of protection appear similar with whole-cell as with acellular pertussis vaccines.